Rice Marketing Efficiency Analysis in Baruga Village, Baruga Subdistrict, Kendari City - M. Dwiki Irdani Juliansyah Imran; Surni, Surni; Hadi Sudarmo (International Journal of Technology and Education Research, 2025)
This study aims to find out 1) how much margin and profit rice traders in Amohalo Village, Baruga District, Kendari City and 2) whether rice marketing in Amohalo Village, Baruga District, Kendari City runs efficiently. This research has been carried out from January to March 2024. The population in this study is rice farmers in Baruga Village, Baruga District, Kendari City. Sampling was carried out using the Simple Random Sampling method. The research sample was 30 paddy rice farmers, while the determination of the trader sample used the Snowball method. The snowball sampling technique is a technique for taking data sources that at first the number is small and then becomes larger. This study uses marketing efficiency analysis (Farmer's Share). The results of the study are: 1) The margin at the mill is Rp2,000/Kg with a profit of Rp1,336/Kg, the wholesaler in channel I with a margin of Rp2,000/Kg and the profit is Rp1,693/Kg, the wholesaler in channel II with a margin of Rp2,000/Kg and the profit is Rp1,673/Kg and the small trader in channel II with a margin of Rp1,333/Kg and the profit is Rp625/Kg and 2) The marketing channel I has a marketing efficiency of 71.42% and the marketing channel II has a marketing efficiency of 65.21% so it can be concluded that both channels have been efficient